Assessment of the reliability of radiographic signs on panoramic radiographs to determine the relationship between mandibular third molars and the inferior alveolar canal - Uzun, Canan; Sumer, Ayse Pinar; Sumer, Mahmut (Elsevier Science Inc, 2020)
Objective. To assess the reliability of radiographic signs of the relationship between impacted mandibular third molars (IMTMs) and the inferior alveolar canal (IAC), and the vertical relationship between IMTM and IAC on panoramic radiographs (PRs) as risk indicators for IAC exposure during extraction. Study Design. Seven radiographic signs regarding the appearance of roots and the IAC were assessed as present or absent on PRs. The vertical relationship between IMTM and the IAC was divided into 3 levels. The correlation between radiographic data and IAC exposure during extraction was analyzed by using chi(2) statistics and logistic regression analysis. Results. In total, 198 IMTMs were examined. In 46 cases (23.2%), the IAC was exposed during extraction. Four radiographic signs-darkening of the root, narrowing of the root, narrowing of the IAC, and diversion of the IAC-were associated with IAC exposure (P <.05). Concurrence of 2 or more of 7 radiographic signs increased the risk of IAC exposure (P <.001). The vertical relationship between IMTM and the IAC was found to be a risk indicator for IAC exposure (P <.001). No significant correlation was found between IAC exposure and inferior alveolar nerve damage (P =.148). Conclusions. Panoramic radiography is useful for assessing the risk of IAC exposure during IMTM extraction.
Keywords: Cone-Beam Ct; Risk-Factors; Nerve Injury; Lingual Nerves; Diagnostic-Accuracy; Extraction; Removal; Surgery; Predict; Images